A Companion to public art - 4 0 16; Knight, Cher Krause,;Senie, Harriet; 5 (Chichester, West Sussex : Wiley, 2016)
A Companion to Public Art is the only scholarly volume to examine the main issues, theories, and practices of public art on a comprehensive scale. -Edited by two distinguished scholars with contributions from art historians, critics, curators, and art administrators, as well as artists themselves -Includes 19 essays in four sections: tradition, site, audience, and critical frameworks -Covers important topics in the field, including valorizing victims, public art in urban landscapes and on university campuses, the role of digital technologies, jury selection committees, and the intersection of public art and mass media -Contains artist's philosophy essays, which address larger questions about an artist's body of work and the field of public art, by Julian Bonder, eteam (Hajoe Moderegger and Franziska Lamprecht), John Craig Freeman, Antony Gormley, Suzanne Lacy, Caleb Neelon, Tatzu Nishi, Greg Sholette, and Alan Sonfist.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: 2 -- 0; 6; Public art. -- 20; 20; Electronic books.;Electronic books